1969
DOI: 10.1021/ja01038a006
|View full text |Cite
|
Sign up to set email alerts
|

Microwave spectrum, structure, and dipole moment of cis-thionylimide

Abstract: The microwave spectrum of thionylimide, HNSO, has been observed and assigned to the planar cis form. The structural parameters are Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1
5

Year Published

1975
1975
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 1 publication
4
18
1
5
Order By: Relevance
“…Ultraviolet absorption spectroscopy of HNSO indicated electronic excitation centered at the S atom [8]. A planar, cis conformation for the HNSO molecule, in agreement with theory, was established from analysis of its microwave spectrum at room temperature [9] and quartic centrifugal distortion constants [10] and the hyperfine constants [11] were determined later. The frequencies of the six fundamental vibrations and a harmonic force field were first derived from low-resolution studies of the IR spectra of HNSO and DNSO in the gas phase [12,13] and in matrices [14].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Ultraviolet absorption spectroscopy of HNSO indicated electronic excitation centered at the S atom [8]. A planar, cis conformation for the HNSO molecule, in agreement with theory, was established from analysis of its microwave spectrum at room temperature [9] and quartic centrifugal distortion constants [10] and the hyperfine constants [11] were determined later. The frequencies of the six fundamental vibrations and a harmonic force field were first derived from low-resolution studies of the IR spectra of HNSO and DNSO in the gas phase [12,13] and in matrices [14].…”
Section: Introductionsupporting
confidence: 61%
“…As first reported from the microwave study [9] HNSO has a cis planar near-prolate structure of C s symmetry.…”
Section: Resultsmentioning
confidence: 57%
“…The same conformation has been found in case of methyl thionyl amine CH3NSO [2]. In this case, no quadru pole coupling constants have ever been reported, whereas for HNSO and DNSO these constants have been determined [1]. The microwave spectrum of thionyl aniline has been assigned by Caminati et al [3], The conformation of this molecule has also been confirmed to be ris-planar, see Figure 1.…”
Section: Introductionsupporting
confidence: 58%
“…The simplest member of this class, H -N = S = 0 , has been studied in some detail by Kirchhoff [1], According to this study, the molecule exists in the gas phase as a planar cis-conformer, i.e., the proton and the oxygen atom are located in a ex position with respect to the N = S double bond. The same conformation has been found in case of methyl thionyl amine CH3NSO [2].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the molecular parameters assumed in these calculations differ significantly from those determined more recently by microwave spectroscopy (3). Secondly, and more important, Eysel (2) employed a computational technique devised by Becher and Mattes (4) which must be regarded with suspicion.…”
Section: Introductionmentioning
confidence: 99%